2010
DOI: 10.1159/000316528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High-Salt Diet on TRPV-1-Dependent Renal Nerve Activity in Dahl Salt-Sensitive Rats

Abstract: Objective: To test the hypothesis that transient receptor potential vanilloid type 1 channel (TRPV1)-mediated increases in afferent renal nerve activity (ARNA) and release of substance P (SP) and calcitonin gene-related peptide (CGRP) from the renal pelvis are suppressed in Dahl salt-sensitive (DS), but not -resistant (DR), rats fed a high-salt (HS) diet. Methods and Results: Male DS and DR rats were given a HS or low-salt (LS) diet for 3 weeks. Perfusion of capsaicin (CAP, 10–6M), a selective TRPV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…21 Rats develop salt-sensitive hypertension after TRPV1 sensory degeneration by capsaicin treatment. 22 Induction of hypertension by deoxycorticosterone acetate treatment in TRPV1 -/-mice aggravated kidney damage. 23 Mutants of TRPV1 not only detected NaCl in the presence of amiloride but also preferred NaCl over water at concentrations avoided by the WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…21 Rats develop salt-sensitive hypertension after TRPV1 sensory degeneration by capsaicin treatment. 22 Induction of hypertension by deoxycorticosterone acetate treatment in TRPV1 -/-mice aggravated kidney damage. 23 Mutants of TRPV1 not only detected NaCl in the presence of amiloride but also preferred NaCl over water at concentrations avoided by the WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, renal afferent nerves were described to act protectively against salt-sensitive hypertension and the structural renal damage of high blood pressure (24,44). A more recent study using a more selective method of renal afferent denervation suggests that this might not be the case, but it could be shown that selective renal afferent denervation was able to blunt the development of deoxycorticosterone acetate-salt hypertension (12).…”
mentioning
confidence: 99%
“…Clinical reports on patients after thermal ablation point to an independent role of afferent renal innervation on blood pressure (33). Experimental data suggest that renal afferent denervation may be protective against the development of high blood pressure (26,42) as well as the progression of renal structural damage in renal disease (6,43). Hence, nonselective thermal ablation of afferent renal nerves in resistant human hypertension may not be always beneficial since the exact pathophysiological situation is normally not well defined (27).…”
mentioning
confidence: 99%